Entrepreneurial Orientation and Motivation to Start Up a Business: Evidence from the Health Service Industry - Marques, C. S. E.; Ferreira, J. J. M.; Ferreira, F.; Lages, M. F. S. (International Entrepreneurship and Management Journal, 2013)
This study aims to investigate the entrepreneurial orientation and motivation to start up a business in a specific group of health care professionals (HCP), namely diagnostic and therapy technicians. Primary data collected through a sample of 367 HCP is used. The results regarding the entrepreneur's psychological and cognitive profile supported the hypothesis that HCP who have previously created a firm have particular psychological and cognitive characteristics conducive to entrepreneurial activity. The results also demonstrate that motivation influences the willingness of firm creation. Additionally, this study highlights some implications for management seeking to promote the emergence of context-relevant conditions that would allow HCP to launch their own business venture more readily.